An intertemporal, multi-region general equilibrium model of agricultural trade liberalization in the South Mediterranean NICs, Turkey, and the European Union - Bayar, Ali; Diao, Xinshen; Yeldan, A. Erinc (International Food Policy Research Institute, 2000)
With the aid of an intertemporal, multi-region general equilibrium model, the authors study issues of agricultural trade liberalization, growth and capital accumulation in the context of a world economy moving towards a multi-polar structure. They specifically focus on Turkey, the European Union, the Middle East, and the Economies in Transition; and study alternative scenarios of formation of customs unions and increased trade orientation. The model is based on intertemporal general equilibrium theory with Ramsey-type dynamics. The world economy is fully endogenized within a 9-region specification, with Turkey, EU, Middle East and the Transition Economies constituting as one of the indigenous regions. A key feature of the model is its explicit recognition of both the commodity and foreign capital flows across regions in an endogenous setting, and its explicit portrayal of the out-of-steady state dynamics under an intertemporal optimization framework. They explore the short- versus the long-run economic impacts of alternative trade and investment policies on agricultural production, foreign trade, resource allocation, accumulation, consumer welfare, and income distribution in the regions of analyis. The results reveal significant gains from increased bilateral trade between the identified regions, and further underscore the crucial importance of financing commodity trade deficits in sustaining the accumulation patterns.